Exercise in the prevention and rehabilitation of breast cancer - Volaklis, Konstantinos A.; Halle, Martin; Tokmakidis, Savvas P. (Wiener Klinische Wochenschrift, 2013)
Breast cancer is the most common type of cancer among women worldwide. Several epidemiological studies have shown an inverse relationship between the risk of breast cancer and physical activity levels, whereas exercise training has been recognized as a significant means in the rehabilitation process of breast cancer survivors. The relative risk reduction of breast cancer for women who engaged in moderate to vigorous physical activity for 3-5 days peek week ranged between 20-40 %. Furthermore, several studies demonstrated a 24-67 % reduction in the risk of total deaths and 50-53 % reduction in the risk of breast cancer deaths in women who are physically active after breast cancer diagnosis compared with sedentary women. Breast cancer survivors should be encouraged to participate in rehabilitation programs in order to obtain numerous physiological and psychological benefits. These include reductions in fatigue and improvements in immune function, physical functioning, body composition, and quality of life. Based on recent scientific evidence, a complete rehabilitation program for patients with breast cancer should combine both strength and aerobic exercise in order to maximize the expected benefits. © 2013 Springer-Verlag Wien.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Breast cancer; Exercise; Prevention; Rehabilitation